Comparison of bicuspidization and Ross procedure in the treatment of unicuspid aortic valve disease in adults – Insight from the AVIATOR registry - Gofus, Ján; Karalko, Mikita; Fila, Petr; Ondrášek, Jiří; Schäfers, Hans-Joachim; Kolesár, Adrian; Lansac, Emmanuel; El-Hamamsy, Ismail; de Kerchove, Laurent; Dinges, Christian; Hlubocký, Jaroslav; Němec, Petr; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Unicuspid aortic valve (UAV) is the second most common underlying cause of aortic valve dysfunction in young adults after the bicuspid valve. The valve may be replaced (for example by pulmonary autograft) or repaired using the bicuspidization technique. The aim of our study was to compare short- and mid-term outcomes of Ross procedure with bicuspidization in patients with severe UAV dysfunction. Methods This was a multi-center retrospective observational cohort study comparing data from two dedicated Ross centers in the Czech Republic with bicuspidization outcomes provided by AVIATOR registry. As for the Ross group, only the patients with UAV were included. Primary endpoint was mid-term freedom from reintervention. Secondary endpoints were mid-term freedom from major adverse events, endocarditis and pacemaker implantation. Results Throughout the study period, 114 patients underwent the Ross procedure (years 2009-2020) and 126 patients underwent bicuspidization (years 2006-2019). The bicuspidization group was significantly younger and presented with a higher degree of dyspnea, a lower degree of aortic valve stenosis and more often with pure regurgitation. The primary endpoint occurred more frequently in the bicuspidization group than in the Ross group - 77.9 vs 97.9 % at 5 years and 68.4 vs 75.2 % at 10 years (p < 0.001). There was no difference in secondary endpoints. Conclusion Ross procedure might offer a significantly lower mid-term risk of reintervention than bicuspidization in patients with UAV. Both procedures have comparable risk of other short- and mid-term complications postoperatively.